The relationship between psychological readiness to return to sport and kinesiophobia in teens and young adults after anterior cruciate ligament reconstruction - Butler, Lauren; Baez, Shelby; Walker, Cody; Roman, Dylan; Douthit, Taylor; Kuenze, Christopher; Ulman, Sophia; , ARROW (Frontiers in Psychology, 2025)
IntroductionPsychological readiness and kinesiophobia are important variables to consider for return to sport clearance after anterior cruciate ligament (ACL) reconstruction. Both have been associated in adult populations; however, it is unknown if they are associated in teens after ACL reconstruction. Therefore, the purpose of this study was to assess the relationship between psychological readiness and kinesiophobia in teens and young adults after ACL reconstruction.MethodsA retrospective cohort design was used. Participants aged 13–30 years, who were 6–12 months post-ACL reconstruction, who completed the Tampa Scale of Kinesiophobia and the ACL Return-to-Sport after Injury Scale were included from a multi-site registry. Two age groups were established (teen: <19 years, adult: ≥19 years), and psychological readiness was categorized using an ACL Return-to-Sport after Injury Scale cutoff of 77 (<77 = unacceptable). Independent samples t-tests, Pearson correlations, and binary logistic regression were performed to examine associations between kinesiophobia and psychological readiness, and the influences of age, sex, and months since surgery.Results315 participants (54.3% female; 18.3 ± 3.3 years; 8.2 ± 1.9 months post-surgery) were analyzed. ACL Return-to-Sport after Injury Scale and Tampa Scale of Kinesiophobia scores were significantly correlated in both groups (teen: r = −0.59, p < 0.001; adult: r = −0.45, p < 0.001), with no significant difference in the correlation coefficients (z = −1.49). Overall, 47.9% scored below the ACL Return-to-Sport after Injury pass threshold. Each one-point increase in kinesiophobia was associated with a 28% higher likelihood of reporting unacceptable psychological readiness. Adults were twice as likely as teens to report unacceptable psychological readiness.DiscussionGreater psychological readiness was associated with lower kinesiophobia in both teens and young adults. Additionally, nearly half reported poor psychological readiness, highlighting the need for interventions aimed at improving psychological readiness during ACL rehabilitation.